Studies of water-soluble extract of Labisia Pumila var Alata of selected geographic origins - Ade Chandra, Iwansyah (2011)
Labisia pumila(Myrsinaceae)or“kacip Fatimah”,is traditionally used in Malay traditional medicine in the form of decoction as postpartum tonic.Today,it is sold as functional food and beverage in response to consumer interest in its potential health benefits.However, nutrient data on this plant,for example,remains scarce.The aim of this research project was to determine the properties and attributes of water-soluble extracts of Labisia pumila var. alata to reveal its potential health benefits as functional food and beverage.The nutrient composition,total phenolic content,total flavanoid content and antioxidant activities of LP of various sources,viz.,Malaysian and Indonesian origins,were studied to determine the source with specific properties and attributes.PLS and PCA were then used to classify and to understand the correlation between total solid,total acidity,and solubility in cold and hot water, proximate properties,minerals,heavy metals,total phenolic content,and antioxidant activities of Labisia pumila var. alata leaves(LP)due to geographic origin.Based on results obtained,there were no significant difference in yield, total solid,total acidity,and solubility in cold and hot water of lyophilized LP extract due to geographic origin (p>0.05).The extract from Halimun-Salak Mountain,Bogor(LPB) was found to have the highest pH content.LPT was found to have the highest gallic acid value(1.86%),total phenolic content(140.49 mg GAE/g lyophilized plant material), antioxidant activity(FRAP) (17.57 mg GAE/g lyophilized plant material),DPPH(EC50)(78.79 µg/mL),protein (9.87±0.18 %), moisture (10.11±0.06 %), mineral Na (20.20 mg/100 g), K (1128 mg/100 g),Mg(476.1 mg/100g),and Zn (2.32 mg/100 g). The highest values of Ca and Fe were for LP from Pahang (LPR) at 265.8 mg/100g Ca and 41.61 mg/100g Fe, respectively.There was a significant difference(p<0.05) between lyophilized extracts of various geographic origins and proximate content,mineral and heavy metals composition, and antioxidant activities.The PCA models showed data correlated with of Labisia pumila var.alata of various geographic origins and proximate composition,mineral and heavy metals composition,and antioxidant activity.The first two factors(F1 and F2)accounted for 61.25% and 20.48%.The factors loading of F1 had a positive correlation with antioxidant activities (FRAP and DPPH), total phenolic content,moisture,and crude fiber.The strong positive loadings of F2 were total flavonoid content and lipid content.The cluster centroid in cluster analysis(CA) resulted in four groups of Labisia pumila var.alata samples based on geographic origins.